The design of an effective extreme controller mechanism scheme for software defined cognitive radio network - Sibanda, Brian (My University, 2021)
In Software Defined Cognitive Radio Network (SDCRN), network security is a significant issue. This issue arises when Software Defined Network (SDN) architecture integrates with the Cognitive Radio Network (CRN) technology. SDN is designed to improve network resource management, while CRN technology is meant at improving spectrum management. These technologies are vulnerable to several malicious attacks. These attacks include Distributed Denial of Service (DDoS) and Primary User Emulation (PUE). Both the DDoS and PUE can be disrupt services in the SDCRN. To curb these attacks, schemes which hardens the security of SDCRN need to be designed. Thus, in this study we propose a security mechanism called Extreme_Controller_Mechanism (XCM) that reduce the effects of DDoS and PUE. The proposed XCM scheme was designed and evaluated in three simulation environment, the OMNeT++, Octave, and MATLAB simulators. The SDCRN data set was generated using the Neural Network back propagation algorithms. The data set was then used in Matlab to evaluate the effectiveness of the prosed XCM scheme. XCM proved to be effective and efficient at detection and prevention of DDoS and PUE attacks in SDCRN. In terms of memory and processor utilisation, XCM proved to the best when compared to other schemes such as the Advanced Support Vector Machine (ASVM) and deep learning convolution network (CDLN). But in terms of detection time, the ASVM was found to be the best performing scheme. Regarding our test for detection rate, false positive and false negative, the XCM, ASVM and CDLM performed the same. The results of the XCM were therefore the best and superior to the ASVM and CDLM. This can be attributed to the fact that the XCM scheme is optimised for DDoS and PUE attacks. We can therefore conclude that our XCM scheme is the best performing scheme compared to the ASVM and CDLN schemes.
Thesis( M. A. (Computer Science)) -- University of Limpopo , 2021
Keywords: Software defined cognitive radio network; Distributed denial of service; Primary user emulation; Software-defined networking (Computer network technology); Computer networks -- Security measures